RELIGIOUS VALUES SHAPE DIGITAL CURRICULUM MANAGEMENT IN INDONESIAN ISLAMIC EDUCATION: AN INTEGRATIVE REVIEW - Muhammad Husni; Aditya Aroun Kholwani; Ali Masdar Fahim (AL - IBRAH, 2026)
Digital transformation has reshaped curriculum management in Islamic educational institutions, generating tensions between technological efficiency and the spiritual-ethical foundations that define Islamic pedagogy. This study examines how digital technology integration in Islamic curriculum management generates, sustains, or resolves cognitive-spiritual tensions in Indonesian Islamic educational institutions. Using an integrative literature review methodology, 23 peer-reviewed sources published between 2017 and 2026 were systematically identified, screened, and synthesized through thematic analysis from an initial pool of 330] identified records. Findings reveal three key outcomes: first, religious and spiritual orientation consistently overrides technical factors as the primary determinant of technology adoption; second, cognitive costs of digital technology use are relatively context-independent, while spiritual-affective outcomes are highly contingent on deliberate instructional design and institutional management quality; third, productive digital curriculum management operates through three nested mechanisms, humanized instructional design, quality management systems, and institutional Islamic identity alignment. The study proposes reconceptualizing spiritual formation as an operational variable of curriculum management rather than a peripheral aspiration, offering curriculum managers an evidence-based framework that transcends the false choice between digital innovation and Islamic educational integrity.